2019
DOI: 10.1055/a-1007-1694
|View full text |Cite
|
Sign up to set email alerts
|

Utility of autologous fibrin glue and polyglycolic acid sheet for preventing delayed bleeding associated with antithrombotic therapy after gastric ESD

Abstract: Background and study aims Delayed bleeding is one of the most serious adverse events of gastric endoscopic submucosal dissection (ESD), especially in patients taking antithrombotic therapy. This study aimed to evaluate the utility and safety of a shielding method with autologous fibrin glue and polyglycolic acid (PGA) sheets for patients undergoing gastric ESD who are receiving antithrombotic therapy. Patients and methods One hundred twenty-three patients who were treated with gastric ESD while recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…When cells are injected in combination with biomaterials, the biomaterial may even create a physical barrier avoiding loss of cells by efflux, entry, e.g., of urine or bacteria into the wound and prevents bleeding after injection. In gastrointestinal surgery, several studies have demonstrated that fibrin glue effectively prevents bleeding after ESD, avoids the entry of food into the wound, and plays a protective role for structure prevention [57][58][59]. The fibrin glue employed in our studies consisted of two components: (i) a solution of fibrinogen, factor XIII and phosphate buffer and (ii) a solution containing thrombin and CaCl 2 turned out to be the preferred self-polymerizing biomaterial for the clinical application investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…When cells are injected in combination with biomaterials, the biomaterial may even create a physical barrier avoiding loss of cells by efflux, entry, e.g., of urine or bacteria into the wound and prevents bleeding after injection. In gastrointestinal surgery, several studies have demonstrated that fibrin glue effectively prevents bleeding after ESD, avoids the entry of food into the wound, and plays a protective role for structure prevention [57][58][59]. The fibrin glue employed in our studies consisted of two components: (i) a solution of fibrinogen, factor XIII and phosphate buffer and (ii) a solution containing thrombin and CaCl 2 turned out to be the preferred self-polymerizing biomaterial for the clinical application investigated here.…”
Section: Discussionmentioning
confidence: 99%
“…In the shielding group, the incidence of delayed bleeding was lower (1/38, 2.6%) than in the conventional group (12/85, 14.1%) and no adverse events associated with endoscopic shielding were observed. 33 Polysaccharide hemostatic powder is a topic hemostatic method that has been investigated in the prevention of post-ESD bleeding. In a Korean study, after dissection of the lesion, hemostasis using hemostatic forceps was done if there was bleeding or if there were visible remnant vessels on the postresection surface and after that, a total of 2 g of absorbable modified polymers particle powder was sprayed onto the postresection surface.…”
Section: How To Decrease Adverse Events?mentioning
confidence: 99%
“…Takimoto and coworkers (66) used PGA sheet and fixed in place with fibrin glue, they found that the PGA sheets were still attached to the ulcer at 3 weeks after treatment. Kikuchi et al (67) combined the autologous FG and PGA sheet to prevent post-ESD bleeding in patients with antithrombotic therapy. They first immersed the lesion size-matched PGA sheet in the autologous fibrinogen, then attached it onto the lesion and fixed it with clip, they finally sprayed the autologous fibrinogen and thrombin to the PGA sheet.…”
Section: Esd Ulcer Shieldingmentioning
confidence: 99%